Nova generacija tehnik določanje nukleotidnega zaporedja: korak k osebni medicini - Berlec, Aleš (Farmacevtski vestnik, 2010)
Determination of the nucleotide sequence of individualćs genome could contribute to the establishment of personalized medicine. High price of the nucleotide sequencing represented the biggest hurdle in the past; however the next generation sequencing techniques have caused the prices to drop. New techniques enable high-throughput parallel sequencing, which makes the processfaster and cheaper. Parallelism is generally accomplished by cyclic array sequencing, where the DNA fragments are attached to the surface or array. DNA fragments are locally multiplied by the use of emulsion or bridge PCR. Fluorescently labelled nucleotides, which are additionally chemically modified in a way, which enables reversible termination of DNA polymerisation,are used. Other techniques are being developed, which enable real-time sequencing and do not require local amplification of DNA fragments. Next generation techniques are limited by shorter read length and higher errorfrequency. This is however compensated by a vast number of parallel reads. The development of sequencing techniques has outpaced the development of their potential applications. Their true value will therefore be seen in the future.
Keywords: človeški genom; nukleotidno zaporedje; sekvenciranje DNA; tehnike